2016
DOI: 10.1111/epi.13444
|View full text |Cite
|
Sign up to set email alerts
|

Ketogenic diet treatment increases longevity in Kcna1‐null mice, a model of sudden unexpected death in epilepsy

Abstract: Summary Individuals with poorly controlled epilepsy have a higher risk for Sudden Unexpected Death in Epilepsy (SUDEP). With approximately one third of people with epilepsy not achieving adequate seizure control with current anti-seizure drugs, there is a critical need to identify treatments that reduce risk factors for SUDEP. The Kcna1-null mutant mouse lacking the potassium channel Kv1.1alpha subunit model risk factors and terminal events associated with SUDEP. In the current study, we demonstrate the progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(85 citation statements)
references
References 28 publications
5
78
1
1
Order By: Relevance
“…In the current study, we aimed to determine whether the KD changes PPARγ expression in the brains of epileptic and normal mice; and, if so, whether it contributes to the anti-seizure effects of the KD. Treating epileptic Kv1.1KO mice for two weeks with a KD reduced seizures by ~70% as we have reported previously (Fenoglio-Simeone et al, 2009b; Kim et al 2015; Simeone et al, 2016). KD-treatment increased PPARγ2 in both genotypes resulting in PPARγ2/γ1 ratios that were 2-fold and 6-fold higher for WT and Kv1.1KO brain compared to SD-fed WT mice.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In the current study, we aimed to determine whether the KD changes PPARγ expression in the brains of epileptic and normal mice; and, if so, whether it contributes to the anti-seizure effects of the KD. Treating epileptic Kv1.1KO mice for two weeks with a KD reduced seizures by ~70% as we have reported previously (Fenoglio-Simeone et al, 2009b; Kim et al 2015; Simeone et al, 2016). KD-treatment increased PPARγ2 in both genotypes resulting in PPARγ2/γ1 ratios that were 2-fold and 6-fold higher for WT and Kv1.1KO brain compared to SD-fed WT mice.…”
Section: Discussionsupporting
confidence: 82%
“…Seizure severity was scored using a modified Racine scale: 0-normal; 1-myoclonic jerk; 2-side-to-side head movement; 3-forelimb/hindlimb clonus, tail extension, a single rearing event; 4-continuous rearing and falling; 5-severe tonic-clonic seizures. To weigh the incidence and severity of seizures, seizure burden index (SBI) scores were calculated using the equation: SBI = [Σ(σ i γ i )]/ε, where σ indicates the severity; i indicates each stage of seizure (1–5); γ is the frequency; and ε indicates the total number of epochs scored as we have described (Simeone et al, 2014a; Roundtree et al, 2016; Simeone et al, 2016). …”
Section: Methodsmentioning
confidence: 99%
“…Strikingly, KD therapy was found to postpone disease progression, delay the onset of severe seizures and to increase the lifespan of Kcna1-null mice, a model of progressive epilepsy and sudden unexpected death in epilepsy (SUDEP) [45 •• ]. A disease modifying epigenetic mechanism of KD therapy is supported by findings that a predominant increase of DNA methylation is associated with chronic epilepsy in the rat and that KD therapy attenuated seizure progression and ameliorated DNA methylation mediated changes in gene expression [46].…”
Section: Disease Modifying and Epigenetic Mechanismsmentioning
confidence: 99%
“…9,11,12 We have recently demonstrated that seizures progressively become more frequent and severe until the mice die at the early age of postnatal day (P) 42 AE 1.3, 12 although the background strain of the mouse influences the severity of seizures and mortality. 9,10 Kcna1-null (Kcna1 À/À ) mice develop spontaneous recurrent seizures including myoclonic seizures, clonus, and generalized tonicclonic seizures around the third week of their life.…”
Section: Introductionmentioning
confidence: 99%